The updated surgical steps of gasless transaxillary endoscopic thyroidectomy with neck level and region orientation for thyroid cancer - Zhou, Yuqiu; Shui, Chunyan; Ma, Linjie; Cai, Yongcong; Sun, Ronghao; Jiang, Jian; Zeng, Dingfen; Wang, Xu; Xu, Xiaoli; Huang, Pei; Li, Chao (Frontiers in Oncology, 2024)
Introduction We previously made a detailed expansion to the gasless transaxillary endoscopic thyroidectomy(GTET) procedure described in the previous literatures. In this study, we optimized the procedure focused on the limitation of the approach in terms of trauma and lymph node dissection and made a comparison with the early procedure. Materials and methods This paper gave a detailed description of the updated procedure and prospectively collected data about patients with papillary thyroid carcinoma(PTC) performed by the two procedures from December 2020 to April 2023. The differences in surgical outcome, surgical trauma and parathyroid gland(PG) function protection were analyzed. Results Of the 302 patients, 184 underwent with early procedure(EP), and 118 underwent with updated procedure(UP). The surgical outcomes of operative time, time of thyroidectomy and central neck dissection, blood loss, drainage and postoperative hospital stay were shorter in UP than that of the EP. The mean number of lymph nodes retrieved and weight of dissection lymphatic tissue in the UP were significantly more than that in EP without increasing the mean number of metastatic lymph nodes. Postoperative complications did not differ between the two procedures. The UP had more advantages in the identification and preservation of the superior parathyroid gland, however, it did not improve the preservation in situ of the inferior parathyroid gland. The visual analog scale score for pain and the changes among inflammation factors was lower in the UP. Conclusion The UP of GTET could perform safely and efficiently while reducing surgical trauma in selected patients.